Pengaruh Lama Waktu Biofermentasi Chromolaena odorata dengan Sumber Karbon Tepung Putak Terhadap Konsentrasi VFA Persial dan Produksi Gas Metan - Oematan, Nisan N. Y; Benu, Imanuel; Oematan, Gustaf; Dami Dato, Twen O (Animal Agricultura, 2024)
This study aims to evaluate the effect of long biofermentation time of Chromolaena odorata with putak flour carbon source on persial VFA concentration and methane gas production. The method used in this study is an experimental method with Complete Randomized Design (CRD) with 4 treatments and 4 repeats so that there are 16 experimental units. The treatment levels are as follows: LB21 = Biofermentation duration for 21 days (as control), LB14 = Biofermentation duration for 14 days, LB7 = Biofermentation duration for 7 days, LB0 = Biofermentation duration for 0 days. The variables studied were the concentration of acetate, propionate, butyrate, valerate and methane gas production. The results of the study are as follows: LB21: acetate of 12.06 mM, propionate of 2.98 mM, butyrate of 1.22 mM, valerate of 0.35 mM and methane gas production of 2.80 mM; LB14: acetate of 10.60 mM, propionate of 3.04 mM, butyrate of 1.39 mM, valerate of 0.33 mM and methane gas production of 2.48 mM; LB7: acetate of 10.89 mM, propionate of 2.83 mM, butyrate of 0.82 mM, valerate of 0.28 mM and methane gas production of 2.51 mM; LB0: acetate of 14.03 mM, propionate of 3.02 mM, butyrate of 1.59 mM, valerate of 0.30 mM and methane gas production of 3.45 mM. The results of statistical analysis showed that the effect of the length of biofermentation time of Chromolaena odorata with a carbon source of putak flour had no real effect (P>0.05) on the concentration of acetic acid, propionic, butyrate valerate and methane gas production. It was concluded that the length of time of biofermentation with the carbon source of putak flour did not affect the concentration of acetic, propionic, butyric, valerate acids and methane gas production.